New record of the genus parkellus jairajpuri, tahseen & choi (mononchida: mononchidae) with redescription of parkellus menzeli male in Vietnam - Tam, Vu Thi Thanh; Winiszewska, Grazyna (Academia Journal of Biology, 2020)
The genus Parkellus with a redescription of Parkellus menzeli male is recorded and illustrated for the first time from Vietnam. One male of Parkellus menzeli was collected from Y Ty Commune, Bat Xat natural conservation area, Lao Cai Province, northwest Vietnam; its measurements and features corresponded well with the type population from Crasta im Textal, Switzerland and other populations from Poland.